Exertional syncope of an unknown origin in a collegiate women`s basketball player: A level 4 rare events case study - Fetchen-DiCesaro, S.; Ramirez-Del Toro, J.; Washburn, N. (Journal of Athletic Training, 2019)
Background: A 21 year old collegiate women's basketball player reported to the athletic trainer during a pre-season workout describing a feeling of near syncope. Upon examination she was verbally responsive with dyspnea, diz-ziness, tachycardia, pale appearance and visible full body tremors. She had no abnormal fi ndings upon physical exam. She reported overall general malaise and loss of appetite. She further report-ed that these symptoms began 5 months prior while home for break but denies exertional syncope. Lab and diagnostic reports from her PCP were negative for thyroid disease, diabetes, electrolyte abnormalities, anemia or intracranial abnormalities. There is a history of de-pression and disordered eating and she had been taking B-12 injections for the past four months with little improve-ment. Differential Diagnosis: Anemia, hormone imbalance, electrolyte abnor-malities, arrythmia, exertional synco-pe. Treatment: Patient was examined by the team physician within 48 hours with no abnormal fi ndings, instructed to cease physical activity and was sent for a CBC and CMP including magnesium phosphate, B-12 folate, iron, transfer-rin, ferritin, TSF, T4, free T4, CRP and Vitamin D levels all of which were found to be within normal limits. She was referred to our sports cardiologist who concurred with the team physi-cians plan of care and ordered a cardiac stress test, 48-hour Holter monitor and electrocardiogram all with subsequent normal fi ndings. A heads-up tilt table test was ordered but not completed. A transthoracic echocardiogram was con-sidered normal but unable to obtain a subcostal view due to abdominal fl uid collection. Subsequently the patient was sent for an abdominal CT which revealed an abdominal mass diagnosed as an ovarian cyst "the size of a foot-ball". Patient was immediately admitted to the hospital and underwent surgery to remove > 15 cm, 5.90 kg ovarian cyst which was found to be benign on post-op testing. Patient was discharged within 72 hours of surgery with post-op care including transfriction massage for scar tissue management. Patient was allowed to resume light cardiovascular activity at 6 weeks and full activity at 8 weeks including intensive core train-ing. Patient completed the basketball season with minimal issue. Post-season care included continued massage and core strengthening Additionally, she competed on the varsity tennis team for the spring season and reported minimal abdominal discomfort. Uniqueness:Ovarian cysts are somewhat common having been reported to occur in 8% to 18% of all women in the United States with approximately 5% to 10% under-going surgical exploration. This patient did not report typical fi ndings for ovari-an cysts including painful menstruation, dysmenorrhea or pain on palpation. She reported never having had an obstetrical exam. Cardiac symptoms and near-syn-cope were a result of compression of the thoracic and abdominal structures from the ovarian cyst. Conclusions:This clinical case exemplifi es the crit-ical need for athletic trainers to com-plete a thoroughly exhaustive history, physical exam and referral if warranted. This patient did not present with typical fi ndings for an ovarian cyst, and given her exertional symptoms, history of dis-ordered eating and depression seemed more likely to be experiencing an issue psychological or cardiac in nature. An interprofessional plan of care and com-munication were essential for swift di-agnosis and care for this patient leading to a positive post-surgical outcome and successful reentry into athletics.